Menstrual Hygiene Management—Knowledge, Attitudes, and Practices Among Female College Students in Bhutan - Tshomo, Tashi; Gurung, Mongal Singh; Shah, Safieh; Gil-Cuesta, Julita; Maes, Peter; Wangdi, Rinchen; Tobden, Jamba (Frontiers in Reproductive Health, 2021)
Background. Girls and women face substantial menstrual hygiene management (MHM) challenges in low and middle-income countries. These challenges are related to inadequate knowledge, and insufficient water, sanitation and hygiene (WASH) facilities. Currently, literature on MHM among college-attending women in Bhutan is scarce. We aimed to explore knowledge, attitudes, and practices (KAP) of female college students from all ten government colleges of Bhutan, documenting conditions of available MHM facilities, from August to September 2018. Methods: A cross-sectional KAP survey was conducted with a random sample of female students from all years and a random sample of MHM facilities at each college and hostel. A questionnaire was adapted from a similar study conducted with school students in Bhutan. Socio-demographics, overall KAP findings, and differences in KAP between first and final year students were analyzed; college and hostel toilets were reported. Results: 1,010 participants completed the self-administered questionnaire. Comprehensive knowledge of menstruation was low (35.5%). Half (50.3%) reported their mother as source of information and 35.1% of the participants agreed that women should not enter a shrine during menstruation. Approximately 4% of median monthly pocket money was spent on absorbents with 96.9% absorbents wrapped before disposal. Half (55.1%) reported menstruation affecting daily activities and 24.2% missed college due to dysmenorrhea. One fifth of participants (21.3%) reported unavailability of water in college, 80.1% of participants reported absence of soap for hand washing and 24.1% described no bins for disposal. In 33.7% of hostel toilets, participants reported doors missing locks. Our team’s observations had similar findings. Conclusion: Female students living in hostels during college years lose considerable resources during their formative years of learning: time, energy, and money, due to issues of menstruation management. Although the overall understanding of menstruation was low, our participants’ MHM practices scored highly, and the vast majority of them asked for a platform to discuss menstruation. Despite some agreement with menstrual taboos (e.g. visiting shrine), only 5.1% were uncomfortable conversing about MHM. Improved public health knowledge, psychosocial/medical support, and WASH infrastructure with freely available menstrual products could lead to more effective MHM practices among female college students.